Serial Changes in Vitamin D Status in Patients During Severe Acute Respiratory Distress Syndrome and Extracorporeal Membrane Oxygenation - Martina Hermann; Jelena Poslussny; Gernot Gerger; Helmuth Haslacher; Georg Mayrhofer; Verena Eva Tretter; Mathias Maleczek; Cem Ekmekcioglu (Medicina)
Background and Objectives: Therapeutic interventions, such as extracorporeal membrane oxygenation (ECMO) therapy, in patients suffering from severe acute respiratory distress syndrome (ARDS) may reduce their vitamin D levels. Many observational studies have shown associations between poor outcomes and low vitamin D levels in critically ill patients. This retrospective study primarily aimed to investigate the time-dependent changes in vitamin D levels and the correlation of vitamin D levels with disease severity and inflammatory markers in patients suffering from ARDS receiving ECMO therapy. Materials and Methods: This study used a longitudinal approach to assess the serial changes and the correlations of vitamin D levels (25-hydroxyvitamin D (25(OH)D) and 1,25-dihydroxyvitamin D (1,25(OH)2D)) with disease severity and inflammatory markers in 24 invasively mechanically ventilated (IMV) patients treated using ECMO over a period of 17 days. Most of the patients in this study were suffering from severe coronavirus disease 2019 (COVID-19) (n = 19; 79%). Serial blood samples collected during routine blood draws were retrospectively analyzed to assess the dynamics of their vitamin D levels over 17 days of ICU therapy. Results: Hypovitaminosis D (25(OH)D ≤ 50 nmol/L) was prevalent in 18 (75%) patients, while values of 25(OH)D lower than 30 nmol/L were measured in 5 patients (21%), indicating severe deficiency. Additionally, 1,25(OH)2D showed a significant decrease within the first 11 days of intensive care unit (ICU) treatment (these levels dropped by 28%; p = 0.03) and then remained at similar levels throughout the observational period; 25(OH)D levels remained largely unchanged during the observation period. We observed that 25(OH)D showed a significant negative correlation with C-reactive protein (CRP) (p = 0.04), and that 25(OH)D and 1,25(OH)2D levels did not show correlations with disease severity. Conclusions: Patients suffering from severe COVID-19 ARDS showed a significant decrease in their 1,25(OH)2D levels from day 0 to day 11 in the ICU. Therefore, routine vitamin D substitution and monitoring in critically ill patients, especially for patients suffering from ARDS treated with ECMO, should be carried out to prevent hypovitaminosis D. In addition, vitamin D may be associated with inflammation. Further studies are necessary to elucidate the mechanisms behind these retrospective observations.